Galatella malacitana (Asteraceae): a new species from the peridotitic mountains of southern Spain - Blanca, Gabriel; Gavira, Óscar; Suárez-Santiago, Víctor N. (Phytotaxa, 2015)
A new species of the genus Galatella is described, illustrated, and compared with the other three Iberian taxa of the genus, G. aragonensis, G. linosyris, and G. sedifolia subsp. sedifolia, and the two morphologically most similar taxa, G. sedifolia subsp. biflora and G. regelii. The new species occurs on peridotitic soils, forming part of the open shrublands in the province of Málaga (southern Spain). In addition, a distribution map, illustrations, and a description of the habitat of the new species are presented. We also propose to use the presence or absence of hairs on the outer surface of the corolla as a diagnostic character in Galatella.